On the (in)efficiency of cryptocurrencies: have they taken daily or weekly random walks?. Issue 4 (April 2021) - Apopo, Natalya; Phiri, Andrew
Abstract: The legitimacy of virtual currencies as an alternative form of monetary exchange has been the centre of an ongoing heated debated since the catastrophic global financial meltdown of 2007–2008. Our study tests the informational market efficiency of cryptomarkets by investigating the weak-form efficiency of the top-five cryptocurrencies using random walk testing procedures which are robust to asymmetries and unobserved smooth structural breaks. Moreover, our study employs two frequencies of cryptocurrency returns, one corresponding to daily returns and the other to weekly returns. Our findings validate the random walk hypothesis for daily series hence validating the weak-form efficiency for daily returns. On the other hand, weekly returns are observed to be stationary processes which is evidence against weak-form efficiency for weekly returns. Overall, our study has important implications for market participants within cryptocurrency markets. Abstract : Efficient market hypothesis (EMH); Cryptocurrencies; Random walk model (RWM); Flexible fourier form (FFF) unit root tests; Smooth structural breaks.